2020
DOI: 10.3390/app10124398
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biofuel Industry Wastes as Alternative Nutrient Sources for DHA-Yielding Schizochytrium limacinum Production

Abstract: The simultaneous use of crude glycerol and effluent from anaerobic digestate, both wastes derived from the biofuel industry, were tested in the frame of circular economy concept, as potential low-cost nutrient sources for the cultivation of rich in docosahexaenoic acid (DHA) oil microalgae strain Schizochytrium limacinum SR21. Initially, the optimal carbon and nitrogen concentration levels for high S. limacinum biomass and lipids production were determined, in a culture media containing conventional, high cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…In our study, S. limacinum SR21 strain was able to grow well on crude glycerol and to accumulate fatty acids for almost 60% of its DCW. This result is aligned with findings from Sun et al (2014) and Bouras et al (2020), who reported that this strain could accumulate lipids for up to 50% of its cell dry matter, in a short time, with a DHA output of 34% of the total lipid concentration. Our analysis of fatty acid profiles showed that palmitic acid and DHA were the major fatty acids produced by the strain.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, S. limacinum SR21 strain was able to grow well on crude glycerol and to accumulate fatty acids for almost 60% of its DCW. This result is aligned with findings from Sun et al (2014) and Bouras et al (2020), who reported that this strain could accumulate lipids for up to 50% of its cell dry matter, in a short time, with a DHA output of 34% of the total lipid concentration. Our analysis of fatty acid profiles showed that palmitic acid and DHA were the major fatty acids produced by the strain.…”
Section: Discussionsupporting
confidence: 91%
“…Comparison of estimated proximate composition between each studied species and estimated values from decapod crustaceans present in the Mediterranean was performed with one sample t-test. Statistical analyses were performed using jamovi [39,40] at an alpha level of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have also been justified in Mata et al (2010); Sakarika and Kornaros (2019). • Schizochytrium limacinum SR21: is considered as a low-cost nutrient cultivation source that produces high averages of docosahexaenoic acid (DHA) and total lipid content reaching high average levels with varying effluent concentrations (Bouras et al, 2020). • Arthrospira (Spirulina) Platensis strains such as Chlorococcum sp.…”
Section: Logical Architecture Of the System And Case Studymentioning
confidence: 97%